2018
DOI: 10.3389/fonc.2018.00407
|View full text |Cite
|
Sign up to set email alerts
|

Methylseleninic Acid Sensitizes Ovarian Cancer Cells to T-Cell Mediated Killing by Decreasing PDL1 and VEGF Levels

Abstract: Redox active selenium (Se) compounds at sub toxic doses act as pro-oxidants with cytotoxic effects on tumor cells and are promising future chemotherapeutic agents. However, little is known about how Se compounds affect immune cells in the tumor microenvironment. We demonstrate that the inorganic Se compound selenite and the organic methylseleninic acid (MSA) do not, despite their pro-oxidant function, influence the viability of immune cells, at doses that gives cytotoxic effects in ovarian cancer cell lines. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
0
13
1
Order By: Relevance
“…In addition, Se increases the expression levels of MHC-I antigens on cancer cells in vitro, thus, improving their detection and destruction by CD8 þ T-lymphocytes [61] (Table 2). Furthermore, an in vitro study showed that methylseleninic acid-enhanced T cell-mediated killing of ovarian cancer cells via PD-L1 and VEGF inhibition [62].…”
Section: Lymphocytesmentioning
confidence: 99%
“…In addition, Se increases the expression levels of MHC-I antigens on cancer cells in vitro, thus, improving their detection and destruction by CD8 þ T-lymphocytes [61] (Table 2). Furthermore, an in vitro study showed that methylseleninic acid-enhanced T cell-mediated killing of ovarian cancer cells via PD-L1 and VEGF inhibition [62].…”
Section: Lymphocytesmentioning
confidence: 99%
“… 5 , 6 Several studies have focused on inflammatory infiltrate, T cells and tumor-associated macrophage (TAM) expression on both OC cell lines and in vivo . 7 PD1 is implicated in programmed cell death and PD1/ PD-L1 is an important immune checkpoint in proliferation and development tumor. 8 Tumor cells with PD-L1 transmembrane protein bind to the PD-1 receptor of T lymphocytes and inactivate them.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al stated that selenium can decrease EGFR expression in tumor cells and cancer metastasis [ 51 ]. Nair et al reported that methylselenic acid and selenite can decrease PD-L1 and VEGF expressions in cancer cells [ 52 ]. Given lung cancer cells which are resistant to EGFR tyrosine kinase inhibitors, Liao et al discovered that the combination of selenium and n-3 PUFA was able to reverse the acquired resistance in cancer cells [ 53 ].…”
Section: Discussionmentioning
confidence: 99%